Estudio de prefactibilidad para la instalación de una planta de producción de té verde de hojas de moringa (Moringa oleifera) - Camargo Diaz, Francisco Manuel (2023)
The main objective of this pre-feasibility study is to determine the feasibility of the project for the installation of a green tea production plant based on Moringa Oleifera in order to supply the demand of the Peruvian market. The final product under study consists of a hermetically sealed doypack bag of green tea based on Moringa Oleifera in a presentation of 100 grams, which has several properties that bring health benefits. It should be noted that it will be marketed on the website and health food stores located in Metropolitan Lima and Callao. To calculate the demand, a survey was carried out as part of the market study to obtain the estimated demand of the project for its useful life, established in five years, being 11.36 tons of green tea for the last year. On the other hand, the location of the plant in the department of Lim was established, taking into consideration several relevant factors for decision making. According to the project engineering, the production process was established, which is semiautomatic and includes machinery, equipment, and qualified personnel to obtain the final product. Additionally, the administration and organization of the company was defined, being an S.A.C., which has a total of nine collaborators between operative and administrative positions. Finally, in relation to the economic and financial chapter, a financing of 30% and a capital contribution of 70% were established, obtaining indicators such as NPV (S/ 241 414), IRRF (25,48%), B/C (S/ 1,53) and a payback period of 4 years 2 months, which demonstrate the viability of the project under study.